Pharmacological and Antioxidant Activities of Rhus coriaria L. (Sumac) - Seyede Fatemeh Hosseini (Plant Biotechnology Persa, 2021)
Rhus coriaria L. (Anacardiaceae), generally known as sumac, is a commonly used powder spice, condiment, and flavoring agent, especially in the Mediterranean region. Owing to its bountiful beneficial values, R. coriaria (RC) has been used in traditional medicine for the management and treatment of many ailments including hemorrhoids, wound healing, diarrhea, and reduction of blood sugar, cholesterol and uric acid levels. R. coriaria is rich in various classes of phytochemicals including polyphenol compounds, flavonoids, anthocyanins, tannins, organic acids, and many others. By virtue of its bioactive, R. coriaria possesses powerful antioxidant capacities that have ameliorative and therapeutic benefits for many common diseases including neurodegenerative disease, diabetes, and cancer. The purpose of this study is a brief review of the effects of R. coriaria on diabetes, cancer, hyperlipidemia, as well as the study of anti-inflammatory and antioxidant properties of this plant. Due to its mineral elements, neurotransmitters, organic acids and high antioxidant ability, Sumac plant can cause significant changes in various organs of the body when consumed.  To sum up, the findings summarized here can be used as a useful dietary supplement and an attractive target for drug discovery.